Urine Tenofovir Levels Strongly Correlate With Virologic Suppression in Patients With Human Immunodeficiency Virus on Tenofovir Alafenamide-Based Antiretroviral Therapy. (18th October 2022) - Johnson, Kelly A; Okochi, Hideaki; Arreguin, Mireya; Watabe, Joseph; Glidden, David V; Chattopadhyay, Anindita; Imbert, Elizabeth; Hickey, Matthew D; Gandhi, Monica; Spinelli, Matthew
Abstract: We found that urine tenofovir (TFV) levels >1500 ng/mL strongly predict virologic suppression among people with human immunodeficiency virus taking tenofovir alafenamide (odds ratio, 5.66; 95% confidence interval, 1.59–20.14; P = .007). This suggests an existing point-of-care assay developed for tenofovir disoproxil fumarate will support adherence monitoring for patients on all TFV-based antiretrovirals.